GREEN EMOTIONAL CLASS AS A LEARNING ENVIRONMENT THAT SUPPORTS LEARNERS’ CREATIVITY - Ibrahim, Maryam; Park, Suhong (Sanata Dharma University Yogyakarta, 2024)
Creativity is involved whenever we try something new, so it is an inherent part of learning. Scholars and educators have acknowledged the importance of the learning environment, especially the creative learning environment, on student creativity. The green emotional class was designed to foster creativity while promoting positive emotions and nature awareness in a fun learning environment for young learners. The learning environment was assessed using observation and survey methods based on the physical environment, learning climate, and learners' engagement. Results showed that the teacher's cheerful disposition and guidance made learners comfortable expressing creativity and exploring nature. So, promoting green emotion in the classroom fosters a creative and fun learning environment.